Main factors of Kota Kinabalu residents tend to use public transport - Mohd Azizul Ladin; Siti Nurmasyittah Ag Besar; Noor Sheena Herayati Harith; Nurmin Bolong; Ismail Saad; Nazaruddin Taha (Academia Industry Networks, 2021)
Transportation and movement of goods are one of the essential human needs, and special attention is placed on the planning of a large city. It has always played an essential role in the development of society, initially concerning trade routes and harbor, but more recently about land and air-based systems. Therefore, in a particular area where the population growth keeps increasing as in Kota Kinabalu, there is a need to implement a good transportation system to ensure proper traffic flow. This paper surveys the reaction of 450 respondents towards the existing public transportation provided in Kota Kinabalu city through a questionnaire distributed via online form. The main aim of this research is to find out the main factor of Kota Kinabalu residents tends to use public transport. Based on the Chi-square analysis, the age and gender of Kota Kinabalu residents have a significant influence on the frequency of public transport usage in Kota Kinabalu. The results of the study also showed that the main factor of Kota Kinabalu tend to use public transports are the reliability of public transport and its drop-off consistency. Meanwhile, the most factors which need to be enhanced are the cleanliness and comfort of the existing public transport in Kota Kinabalu, Sabah.